Sustainable biodegradable tapioca starch films enhanced with basil oil, carboxymethyl cellulose, and citric acid for functional food packaging applications - Raajeswari, Paramasivam; Manivel, Devatha; Dhanapal, Anto Cordelia Tanislaus Antony; Menkinoska, Marija; Pavlovska, Gorica; Helal, Mahmoud; Sami, Rokayya; Alsanei, Woroud A.; Alessa, Fatima M.; Trajkovska Petkoska, Anka; Qari, Sameer H. (Frontiers in Sustainable Food Systems, 2025)
The study investigated the potential of tapioca starch (Manihot esculenta) as a raw material for food packaging enhanced with basil leaf oil, citric acid, and carboxymethyl cellulose. The objective of this study was to standardize active edible tapioca films and evaluate their physicochemical, textural, and barrier properties (oxygen and water vapor transmission rates), microbial load, brine shrimp lethality assay (BSLA), and biodegradability. Films were produced using a casting technique with tapioca starch (10 g), dried using a film-making machine, and enhanced with 0.1 g citric acid as a crosslinker, 0.5 g carboxymethyl cellulose as a filler, and 1 ml basil leaf oil as an additive. Tapioca film (30 × 21 cm, 0.25 mm thickness) exhibited 3%−5% moisture, 1%−2% ash, and a pH of 5–6, with tensile strengths ranging from 2.48 to 6.28 MPa and elongation at break between 10.36% and 16.75% oxygen transmission rate was 690.05 to 811.14 cc/m2/day, and water vapor transmission rate was 0.73 to 1.21 cm3/m2/24h/0.1 MPa. The inclusion of citric acid, carboxymethyl cellulose, and basil leaf oil improved the tensile strength and barrier properties, making the films suitable for packaging a variety of food products (cereals, legumes, spices, condiments, extruded products, and sugar candies) for up to 120 days. The microbial load remained below 5.7 × 101 CFU/g, with low toxicity (7% in BSLA), and the films degraded completely in moist topsoil within 24 days. This study highlights the tapioca starch films enhanced with carboxymethyl cellulose, citric acid and basil oilas a sustainable alternative to single-use plastics. It provides an effective packaging solution for non-perishable commodities and sugar candies with improved functional properties and environment sustainability.